Economic survival strategies and tactics used by pirate community radio stations in Zimbabwe. Case study Patsaka Nyaminyami Community Radio - Mangwiro, Anesu (Midlands State University, 2020)
Community radio station offers diversity in media content. The plurality in content, offers citizens wide and broad information they are entitled to. Unfortunately, the government of Zimbabwe has not yet licensed any community radio station. Radio piracy in Zimbabwe has mushroomed due to the unfair issuing of broadcasting licenses. Radio production incurs expenses thus Patsaka Nyaminyami Community Radio station (PNCR) has adopted means of surviving economically through various strategies and tactics. This research explores on the various strategies and tactics which have been deployed by PNCR and amongst these strategies include; donor funding, advertising, cost effective programming, expansion of business and the use of volunteers. Competitive advantage theory and democratic participant theory were used to inform this study.